Whirlwinds and Break-Ins: Evidence Linking a New Orleans Tornado to Residential Burglary - Frailing, Kelly (Journal of crime and justice, 2021)
This study examines the number and location of residential burglaries before and after a tornado that struck New Orleans, Louisiana in February 2017. Using calls for service to the New Orleans Police Department, Weather Service data and geospatial referencing, we found that the number of residential burglaries increased in the short-term aftermath of the tornado and that the increase in suitable targets caused by the tornado appears to be an important predictor of post-tornado burglary in that timeframe. We conclude with implications for policy and practice that stem from our findings.